Association between Helicobacter pylori and open angle glaucoma: current perspective - Zaidi, M; Jilani, FA; Gupta, Y; Umair, S; Gupta, M (Nepalese Journal of Ophthalmology, 2010)
Helicobacter pylori is a Gram negative, spiral-shaped, strictly micro-aerophilic and flagellate human pathogen that can inhabit many areas of stomach. H. pylori infection leads to the generation of oxygen free radicals. H. pylori infection might also aggravate the course of glaucoma by increasing the levels of nitric oxide, endothelin-1 and free radicals indirectly. This article briefly reviews the current perspectives on this issue. Keywords: Helicobacter pylori; glaucoma; free radicals DOI: 10.3126/nepjoph.v1i2.3688 Nep J Oph 2009;1(2):129-135